Organic Light-Emitting Diodes Based on Conjugation-Induced Thermally Activated Delayed Fluorescence Polymers: Interplay Between Intra- and Intermolecular Charge Transfer States - Li, Yungui; Wei, Qiang; Cao, Liang; Fries, Felix; Cucchi, Matteo; Wu, Zhongbin; Scholz, Reinhard; Lenk, Simone; Voit, Brigitte; Ge, Ziyi; Reineke, Sebastian (Frontiers in Chemistry, 2019)
In this work, interactions between different host materials and a blue TADF polymer named P1 are systematically investigated. In photoluminescence, the host can have substantial impact on the photoluminescence quantum yield (PLQY) and the intensity of delayed fluorescence (ΦDF), where more than three orders of magnitude difference of ΦDF in various hosts is observed, resulting from a polarity effect of the host material and energy transfer. Additionally, an intermolecular charge-transfer (CT) emission with pronounced TADF characteristics is observed between P1 and 2,4,6-tris[3-(diphenylphosphinyl)phenyl]-1,3,5-triazine (PO-T2T), with a singlet-triplet splitting of 7 meV. It is noted that the contribution of harvested triplets in monochrome organic light-emitting diodes (OLEDs) correlates with ΦDF. For devices based on intermolecular CT-emission, the harvested triplets contribute ~90% to the internal quantum efficiency. The results demonstrate the vital importance of host materials on improving the PLQY and sensitizing ΦDF of TADF polymers for efficient devices. Solution-processed polychrome OLEDs with a color close to a white emission are presented, with the emission of intramolecular (P1) and intermolecular TADF (PO-T2T:P1).